Bleaching and Softening of Coir Fiber Using Averrhoa Bilimbi Extract. Issue 12 (2nd December 2022) - Rajan, Revathy; S, Ajith; Joshy, Annu; R, Anita
ABSTRACT: Bleaching and softening of the hard fiber "Coir" renders it suitable for use in the coir industry, which presently adopts various chemical treatment processes that are not eco-friendly. The present study aims at treatment of coir fibers with Averrhoa bilimbi for enhanced bleaching and softening. The quality of the treated fibers with respect to physical and chemical characterization viz. variation in lignin content, flexural rigidity to assess the degree of softness, light fastness, tensile strength and brightness index has been carried out. The treated fibers displayed remarkable increase in brightness index from 9.45 to 11.19. Removal of surface projections on the coir fiber upon treatment is evident from Scanning Electron Microscope images. These surface changes can be attributed to the fiber softening.